A resin composition and its application
By using a crosslinker with a specific molecular structure in the resin composition and the other components, it is solved the problem of difficult to develop materials with low plane thermal expansion coefficient, low water absorption rate and high glass transition temperature in the prior art. Excellent dielectric performance and dimensional stability of high-frequency and high-speed electronic substrates are achieved.
Patent Information
- Application Number
- CN202111683513.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The prior art is difficult to develop a polymer matrix material with low plane thermal expansion coefficient, low water absorption rate, low dielectric loss tangent, high glass transition temperature and water absorption, which can maintain low dielectric properties, which cannot meet high frequency and high speed electronics. Performance requirements of substrate.
Through the coordinated combination of specific components, the use of crosslinking agents with specific molecular structures and other components is used to cooperate with other components, which significantly reduces the plane thermal expansion coefficient and water absorption rate of the resin composition, increases the glass transition temperature, and after the water absorption is absorbed, the Maintain low dielectric performance.
The resin composition and the metal-covered foil laminate containing the same have excellent dielectric properties and dimensional stability, and are suitable for higher-level high-speed and high-frequency packaging.
Smart Images

Figure BDA0003453718490000031 
Figure BDA0003453718490000081 
Figure BDA0003453718490000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper clad laminates, and in particular relates to a resin composition and application thereof. Background Art
[0002] In recent years, computers and communication equipment have been developing towards high performance and multi-functions. In order to achieve high-speed transmission and large-capacity information processing, operating signals have also tended to be high-frequency, which has put forward higher requirements on electronic circuit substrates. With the advent of the 5G era, represented by high-frequency RF (such as PA, WiGig, WiHD / 60GHz, etc.), large-size chips, DDR5 (3.2~6.4Gbps) and other applications, higher requirements are put forward for the performance of packaging substrate materials: while having a low in-plane thermal expansion coefficient, it must also have a lower dielectric loss tangent.
[0003] The main chain of polyphenylene ether resin contains a large number of benzene rings, has good physical and mechanical properties, as well as lower dielectric constant and dielectric loss tangent, and is a more ideal electronic substrate raw material. However, the melting point of polyphenylene ether resin is higher, the fluidity is poor, and the processing performance is not good enough, resulting in a large melt viscosity of the prepreg containing it, which is difficult to meet the process manufacturing requirements of multilayer printed wiring boards. By reducing the molecular weight of polyphenylene ether resin, the melting temperature can be effectively reduced and the fluidity can be improved, but low molecular weight can cause the heat resistance of polyphenylene ether resin to decrease, which is also unfavorable for the processing and application of printed wiring boards. Therefore, in order to meet the requirements of actual production and processing, it is necessary to modify polyphenylene ether by a blending or chemical grafting method.
[0004] Polyolefin resin does not contain polar groups, has good dielectric properties, low water absorption and good flexibility, and is widely used as a polymer matrix material for circuit boards. Combining it with polyphenylene ether can make the polymer matrix material achieve a good balance in processability and mechanical properties. CN110605880A discloses a thermosetting hydrocarbon polymer composition, firstly reacting a hydroxyl-containing polyphenylene ether, a hydrogenated hydroxyl-terminated polyolefin resin and a vinyl halide under the action of an initiator, and then adding a polydiene resin, a vinyl-modified polyphenylene ether and an initiator to continue the reaction to obtain a thermosetting hydrocarbon polymer composition with adjustable properties; the semi-cured sheet and the copper-clad laminate containing the above composition have good dielectric properties, but the bonding performance of the resin composition is insufficient, and the prepared copper-clad laminate has low peeling strength, which affects the subsequent processability and usability.
[0005] CN111393724A discloses a resin composition and a prepreg and circuit material using the same. The resin composition includes an unsaturated polyphenylene ether resin, a polyolefin resin, a rosin resin and an initiator. The resin composition has good film-forming properties, adhesion and dielectric properties, but the resin composition has a low glass transition temperature, unsatisfactory heat resistance, and a high thermal expansion coefficient, resulting in poor dimensional stability of the circuit material containing the resin composition.
[0006] Maleimide resin is a traditional encapsulation substrate resin system with high monomer activity, and its cured product has a high glass transition temperature and good heat resistance, and can maintain stable performance in a wide temperature range, which helps to improve the thermal expansion of the material. CN102850766A discloses a halogen-free resin composition, including epoxy-modified polyphenylene ether resin, allyl-modified bismaleimide resin, epoxy resin, phosphorus-containing flame retardant, curing accelerator, curing agent and inorganic filler; The resin composition has good compatibility, wettability and heat resistance, but the copper-clad plate containing it has a high dielectric loss tangent, high water absorption, insufficient dielectric properties, and is difficult to meet the performance requirements of high-frequency printed circuit boards. At the same time, in order to still use electronic equipment in an environment with high humidity, it is often not enough to only reduce the water absorption of the printed circuit board, and it is also required that the printed circuit board can still maintain its low dielectric properties even after absorbing water.
[0007] Therefore, developing a polymer matrix material with low planar thermal expansion coefficient, low water absorption, low dielectric loss tangent, high glass transition temperature and the ability to maintain low dielectric properties after absorbing water to meet the performance requirements of high-frequency and high-speed electronic substrates is a research focus in this field. Summary of the invention
[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a resin composition and its application. By synergistically compounding specific components, especially the coordination of a cross-linking agent with a specific molecular structure and other components, the planar thermal expansion coefficient and water absorption rate of the resin composition are significantly reduced, the glass transition temperature is increased, and the low dielectric properties can be maintained after absorbing water, so that the resin composition and the metal foil-clad laminate containing the same have excellent dielectric properties and dimensional stability, and are particularly suitable for higher-level high-speed and high-frequency packaging.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a resin composition, which comprises the following components in parts by weight: 10 to 70 parts of a modified maleimide compound, 10 to 75 parts of a polyphenylene ether containing an unsaturated group, and 5 to 30 parts of a crosslinking agent having a structure represented by formula I in its molecular structure.
[0011]
[0012] In Formula I, R a , R b , R c and R d Each is independently selected from a C1-C5 aliphatic hydrocarbon group or a halogen atom; e and f are each independently selected from an integer of 0 to 3 (e.g., 0, 1, 2, 3); g and h are each independently selected from an integer of 0 to 4 (e.g., 0, 1, 2, 3, 4).
[0013] The C1-C5 aliphatic hydrocarbon group of the present invention may be C1, C2, C3, C4 or C5, and illustratively includes but is not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, etc.
[0014] The halogen atom described in the present invention includes fluorine, chlorine, bromine or iodine; when the same description is referred to below, they have the same meaning.
[0015] In Formula I, the short straight lines on both sides of the group represent the connection sites of the group, not the methyl group.
[0016] The modified maleimide compound of the present invention includes an addition reaction product of a maleimide compound a1 containing at least 2 (e.g., 2, 3 or 4, etc.) N-substituted maleimide groups in one molecule and an amine compound a2 containing at least 2 (e.g., 2, 3 or 4, etc.) primary amino groups in one molecule.
[0017] The cross-linking agent having the structure shown in Formula I in the molecular structure of the present invention contains at least two (e.g., 2, 3, 4, 5, 6 or 8, etc.) reactive groups, and any group that can chemically react with the modified maleimide compound or the polyphenylene ether containing an unsaturated group can be selected.
[0018] The reactive group of the present invention is selected from at least one of an epoxy group, an amino group, a hydroxyl group, an acrylate group, a mercapto group or a carboxyl group. From the perspective of optimizing dielectric properties and increasing glass transition temperature, the reactive group is preferably at least one of an amino group, an acrylate group or a mercapto group. From the perspective of lower dielectric properties and higher glass transition temperature, the reactive group is further preferably an acrylate group.
[0019] The resin composition provided by the present invention comprises a combination of a modified maleimide compound, a polyphenylene ether containing an unsaturated group and a crosslinking agent having a structure shown in Formula I in its molecular structure; wherein the modified maleimide compound comprises an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule, and has good solubility, high reactivity and excellent heat resistance, and the modified maleimide compound and the polyphenylene ether containing an unsaturated group are used as main components, and the dielectric loss tangent and the planar thermal expansion coefficient are small; the crosslinking agent having a structure shown in Formula I in its molecular structure contains a high rigidity group in its molecular structure, which helps to further improve the glass transition temperature of the resin composition and reduce the water absorption rate and the planar thermal expansion coefficient of the resin composition. The resin composition has a lower planar thermal expansion coefficient, a lower water absorption rate and a lower dielectric loss tangent through the synergistic compounding of three components. At the same time, it has a high glass transition temperature and can still maintain low dielectric properties after absorbing water, so that it fully meets the performance requirements of high-frequency and high-speed printed circuit boards and electronic equipment.
[0020] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.
[0021] In the resin composition provided by the present invention, the modified maleimide compound is 10 to 70 parts, for example, it can be 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts or 68 parts, etc.
[0022] In the resin composition provided by the present invention, the polyphenylene ether containing unsaturated groups is 10 to 75 parts, for example, it can be 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts or 74 parts.
[0023] In the resin composition provided by the present invention, the cross-linking agent containing the structure represented by Formula I in the molecular structure is 5 to 30 parts, for example, it can be 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts.
[0024] Preferably, the maleimide compound a1 contains two N-substituted maleimide groups in one molecule, which can give the modified maleimide compound better fluidity and solubility.
[0025] Preferably, the maleimide compound a1 includes N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane methane, bis(3-ethyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(4-maleimidophenoxy)benzene, 1,3-bis(3-maleimidophenoxy)benzene, bis(4-(3-maleimidophenoxy)phenyl)methane, bis(4-(4-maleimidophenoxy) 1,1-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleimidophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)butane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)butane, 4,4'- Any one or a combination of at least two of bis(3-maleimidophenoxy)biphenyl, 4,4'-bis(4-maleimidophenoxy)biphenyl, bis(4-(3-maleimidophenoxy)phenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)ketone, bis(4-(3-maleimidophenoxy)phenyl)ether or bis(4-(4-maleimidophenoxy)phenyl)ether, and further preferably any one or a combination of at least two of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane or 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane.
[0026] Preferably, the amine compound a2 includes a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-5,5'-diethyl -4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl or 4,4'-diamino-3,3'-dihydroxybiphenyl, or any one or a combination of at least two thereof; further Preferred is any one of a siloxane compound containing at least two primary amino groups, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, or 2,2-bis(4-(4-aminophenoxy)phenyl)propane, or a combination of at least two thereof.
[0027] Preferably, the amine compound a2 includes a siloxane compound having two primary amino groups in one molecule, and more preferably includes a siloxane compound having two primary amino groups at the molecular end.
[0028] As a preferred technical solution of the present invention, the amine compound a2 includes a siloxane compound containing two primary amino groups, and a resin composition with a low planar expansion coefficient can be obtained. The siloxane compound containing two primary amino groups can be a commercially available product, exemplarily including but not limited to: PAM-E (side chain methyl type, functional group equivalent 130g / mol), KF-8010 (side chain methyl type, functional group equivalent 430g / mol), X-22-161A (side chain methyl type, functional group equivalent 800g / mol), X-22-161B (side chain methyl type, functional group equivalent Any one of KF-8012 (side chain methyl type, functional group equivalent weight 1500 g / mol), KF-8008 (side chain methyl type, functional group equivalent weight 5700 g / mol), X-22-1660B-3 (side chain phenyl type, functional group equivalent weight 2200 g / mol) or X-22-9409 (side chain phenyl type, functional group equivalent weight 670 g / mol) or a combination of at least two thereof.
[0029] Preferably, based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the cross-linking agent containing the structure represented by Formula I in the molecular structure, the amount of the siloxane compound is 1 to 30 parts, for example, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts or 28 parts, etc., more preferably 2 to 15 parts, which can make the resin composition have a low planar thermal expansion coefficient and good fluidity.
[0030] In the modified maleimide compound of the present invention, the addition reaction of the maleimide compound a1 containing at least 2 N-substituted maleimide groups in one molecule and the amine compound a2 containing at least 2 primary amino groups in one molecule is preferably carried out in an organic solvent; the type of the organic solvent is not particularly limited, and from the perspective of solubility and volatility, propylene glycol monomethyl ether is further preferred.
[0031] In the present invention, the temperature of the addition reaction of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited, as long as the maleimide compound a1 and the amine compound a2 react. As a preferred technical scheme of the present invention, from the perspective of reaction rate and solvent boiling point, preferably, the temperature of the addition reaction is 100-130°C, for example, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C or 128°C, etc.
[0032] In the present invention, the addition reaction time of the maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and the amine compound a2 containing at least two primary amino groups in one molecule is not particularly limited. Preferably, the addition reaction time is 2 to 10 hours, for example, it can be 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, etc., and more preferably 3 to 8 hours.
[0033] Preferably, the polyphenylene ether containing an unsaturated group has a structure as shown in Formula II:
[0034]
[0035] In formula II, R3, R4, R5, and R6 are each independently selected from hydrogen, a C1-C8 (e.g., C1, C2, C3, C4, C5, C6, C7, or C8) straight chain or branched alkyl group.
[0036] m and n represent the number of repeating units, and are independently selected from 0 to 100, for example, 2, 5, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, etc.; and m and n are not 0 at the same time.
[0037] A1 and A2 are each independently selected from any one of the following groups:
[0038]
[0039] Wherein, p and q are each independently selected from integers of 0 to 8, for example, 0, 1, 2, 3, 4, 5, 6, 7 or 8. When p is 0, it means that the benzene ring is connected to the main chain of formula II through a single bond; when q is 0, it means that the alkenyl group is connected to the main chain of formula II through a single bond.
[0040] In the present invention, the short straight lines on one or both sides of the group (such as The short straight line on the right, The short straight lines on both sides represent the access bonds of the group, not the methyl group; the same expressions mentioned below have the same meaning.
[0041] R7, R8, and R9 are each independently selected from hydrogen, C1-C8 (e.g., C1, C2, C3, C4, C5, C6, C7 or C8) linear or branched alkyl.
[0042] M is selected from a carbonyl group, a C6-C18 (e.g., C6, C9, C10, C12, C14, C16, or C18, etc.) arylene group, or a C1-C10 (e.g., C1, C2, C3, C4, C5, C6, C7, C8, C9, C10) straight chain or branched alkylene group.
[0043] Z is selected from
[0044] X is selected from C1-C20 (e.g., C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18, or C19, etc.) straight or branched alkylene, C3-C20 (e.g., C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18, or C19, etc.) cycloalkylene, C2-C20 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18, or C19, etc.) heterocycloalkylene, or one or at least two non-adjacent -CH2- in the C1-C20 straight or branched alkylene is replaced by -O-, -S-, -CO-, Alternative groups.
[0045] The heteroatoms in the C2-C20 heterocycloalkylene group include O, S, N, P or Si.
[0046] R Z1 , R Z2 , R Z3 , R Z4 , R Z5 , R Z6 , R Z7 , R Z8 , R N , R P , R S1 , R S2 Each is independently selected from hydrogen, C1-C8 (eg, C1, C2, C3, C4, C5, C6, C7 or C8) straight chain or branched alkyl.
[0047] Preferably, A1 and A2 are each independently selected from Any one of .
[0048] Preferably, said R9 is selected from hydrogen or methyl.
[0049] As a preferred technical solution of the present invention, A1 and A2 are each independently selected from any one of vinylbenzyl, vinylphenyl, acrylate or methacrylate.
[0050] Further preferably, at least one of A1 and A2 is That is, the polyphenylene ether containing an unsaturated group is a polyphenylene ether containing a vinyl benzyl group (such as p-vinyl benzyl or m-vinyl benzyl) at the end, which can better improve the dielectric properties and heat resistance of the resin composition. The polyphenylene ether containing a vinyl benzyl group at the end can be a commercially available product, exemplarily including but not limited to: OPE-2st 1200 (number average molecular weight M n 1200) and / or OPE-2st 2200 (number average molecular weight M n is 2200) etc.
[0051] Preferably, the number average molecular weight of the polyphenylene ether containing unsaturated groups is 500-3000, for example, 600, 800, 1000, 1100, 1300, 1500, 1700, 1900, 2000, 2100, 2300, 2500, 2700 or 2900.
[0052] Preferably, based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the cross-linking agent containing the structure represented by formula I in the molecular structure, the amount of the modified maleimide compound is 10 to 70 parts, for example, it can be 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts or 68 parts, etc. From the perspective of low dielectric properties and low water absorption, reduced curing difficulty and meeting heat resistance requirements, it is further preferably 10 to 50 parts.
[0053] If the content of the modified maleimide compound is too low, the glass transition temperature of the resin composition is low; if the content of the modified maleimide compound is too high, the dielectric loss tangent of the resin composition will increase, affecting the dielectric properties.
[0054] Preferably, based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the cross-linking agent containing the structure represented by Formula I in the molecular structure, the amount of the polyphenylene ether containing an unsaturated group is 10 to 75 parts, for example, it can be 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts or 74 parts, etc., and from the perspective of low planar thermal expansion coefficient and high heat resistance, it is further preferably 10 to 50 parts.
[0055] If the content of the polyphenylene ether containing unsaturated groups is too low, the dielectric constant and dielectric loss tangent of the resin composition are high, and the dielectric properties are poor, making it difficult to meet the requirements of high-speed applications; if the content of the polyphenylene ether containing unsaturated groups is too high, the glass transition temperature of the resin composition will be reduced, affecting the reliability of the laminate.
[0056] Preferably, based on the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the cross-linking agent containing the structure represented by formula I in the molecular structure as 100 parts by weight, the amount of the cross-linking agent containing the structure represented by formula I in the molecular structure is 5 to 30 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts, etc.
[0057] In the resin composition, a specific amount of a cross-linking agent containing a structure shown in Formula I in the molecular structure cooperates with a modified maleimide compound and a polyphenylene ether containing an unsaturated group, which can reduce the planar thermal expansion coefficient and water absorption and increase the glass transition temperature. If the content of the cross-linking agent containing a structure shown in Formula I in the molecular structure of the resin composition is too low, the glass transition temperature of the resin composition cannot be effectively increased, and the planar thermal expansion coefficient and water absorption of the resin composition cannot be reduced; at the same time, due to the decrease in the curing cross-linking density of the resin composition, the glass transition temperature of the resin composition tends to be further reduced. If the content of the cross-linking agent containing a structure shown in Formula I in the molecular structure is too high, the dielectric loss tangent of the resin composition increases, and the thermal curing reaction is insufficient due to the excess of unreacted groups, which affects the reliability of the resin composition, laminated board, metal foil-clad laminated board and printed circuit board.
[0058] Preferably, the resin composition further includes 0.5 to 40 parts by weight of an auxiliary crosslinking agent, for example, the auxiliary crosslinking agent may be 0.8, 1, 3, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35 or 38 parts, etc.
[0059] In the present invention, the auxiliary crosslinking agent is not particularly limited, as long as it can cause the composition to undergo a crosslinking reaction. As a preferred technical solution of the present invention, the auxiliary crosslinking agent includes a crosslinking agent and / or a cyanate ester having a carbon-carbon unsaturated double bond in the molecule.
[0060] Preferably, the crosslinking agent having a carbon-carbon unsaturated double bond in the molecule includes any one or a combination of at least two of a multifunctional vinyl compound, an allyl compound, other acrylate compounds, a trialkenyl isocyanurate compound, other maleimide compounds, an acenaphthylene compound or polybutadiene.
[0061] Preferably, the other acrylate compounds include tricyclodecane dimethanol methacrylate, the structural formula of which is:
[0062]
[0063] Preferably, the allyl compound comprises triallyl isocyanurate.
[0064] In the resin composition of the present invention, the crosslinking agent containing the structure shown in Formula I in the molecular structure has a crosslinking effect, and can be used as a crosslinking agent alone or together with an auxiliary crosslinking agent (other acrylate compounds and / or allyl-containing compounds).
[0065] Based on the performance stability of the resin composition under heat treatment, as well as comprehensive considerations such as the glass transition temperature, planar thermal expansion coefficient and water absorption, preferably, based on the total amount of the cross-linking agent and the auxiliary cross-linking agent containing the structure represented by Formula I in the molecular structure as 100 parts by weight, the amount of the cross-linking agent containing the structure represented by Formula I in the molecular structure is ≥50 parts, for example, it can be 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts or 98 parts, etc., and is further preferably 70 to 100 parts.
[0066] Preferably, the resin composition further comprises 2 to 30 parts of polyolefin resin by weight, for example, the polyolefin resin may be 3 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts.
[0067] As a preferred technical solution of the present invention, the polyolefin resin helps to improve the dielectric properties of the resin composition. However, if the content of the polyolefin resin is too high, the adhesion between the resin composition and the metal foil is reduced, and at the same time, the melt fluidity of the resin composition is reduced, which is not conducive to preparing a resin composition with uniform thickness.
[0068] Preferably, the polyolefin resin includes a styrene copolymer. A styrene copolymer is, for example, a copolymer including an olefin structural unit and a styrene structural unit. The olefin structural unit is derived from an olefin monomer, such as a structural unit derived from butadiene, a structural unit derived from isoprene, etc.; the styrene structural unit is derived from a styrene monomer, such as a structural unit derived from styrene, a structural unit derived from styrene with a substituent, etc. In addition to containing structural units derived from olefin structural units and styrene structural units, styrene copolymers may also contain structural units other than olefin structural units and styrene structural units, such as structural units derived from epoxy groups, structural units derived from amino groups, structural units derived from maleic anhydride, etc.
[0069] The styrenic copolymer may be a random copolymer or a block copolymer. If the styrenic copolymer is a random copolymer, the styrenic copolymer is a copolymer in which a plurality of olefin structural units and a plurality of styrenic structural units are randomly arranged. If the styrenic copolymer is a block copolymer, the styrenic copolymer is a copolymer in which one or more olefin blocks and one or more styrenic blocks are arranged. The olefin block is composed of a plurality of olefin structural units, and the styrenic block is composed of a plurality of styrenic structural units.
[0070] The structural unit from olefin of the polyolefin resin can be hydrogenated or partially hydrogenated. Based on the consideration of dielectric properties, the structural unit from olefin of the polyolefin resin can be preferably hydrogenated. The polyolefin resin can be a commercially available product, exemplarily including but not limited to: Ricon 153 (butadiene copolymer, Cray Valley), Ricon 100 (butadiene-styrene copolymer, Cray Valley), Ricon 181 (butadiene-styrene copolymer, Cray Valley), Tuftec H1051 (hydrogenated styrene-butadiene copolymer, the mass percentage of styrene is 42%, Asahi Kasei Chemicals Co., Ltd.) or Tuftec M1913 (hydrogenated styrene-butadiene copolymer with maleic anhydride structural unit, the mass percentage of styrene is 30%, Asahi Kasei Chemicals Co., Ltd.) any one or a combination of at least two thereof.
[0071] Preferably, the resin composition further comprises 0.01 to 5 parts of a curing accelerator by weight, for example, the curing accelerator may be 0.03 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 4.8 parts, etc.
[0072] Preferably, the curing accelerator includes any one of an acidic curing accelerator, an organic phosphorus curing accelerator, an imidazole curing accelerator, a pyridine curing accelerator, an amine curing accelerator, a peroxide or an organic metal salt, or a combination of at least two thereof.
[0073] For example, the acidic curing accelerator includes p-toluenesulfonic acid, etc.; the organophosphorus curing accelerator includes triphenylphosphine, etc.; the imidazole curing accelerator includes imidazole or imidazole derivatives (such as 2-ethyl-4-methylimidazole); the pyridine curing accelerator includes pyridine or pyridine derivatives (such as 4-dimethylaminopyridine); the amine curing accelerator includes secondary amine compounds, tertiary amine compounds or quaternary ammonium salts; the peroxide includes diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane or α,α'-bis(tert-butylperoxy)diisopropylbenzene, etc.; the organic metal salt includes zinc naphthenate, cobalt naphthenate, tin octoate or cobalt octoate, etc. The curing accelerator can be used alone or in combination of at least two.
[0074] Preferably, the resin composition further comprises 5 to 250 parts of inorganic fillers by weight, for example, the inorganic filler can be 8 parts, 10 parts, 20 parts, 30 parts, 50 parts, 70 parts, 90 parts, 100 parts, 110 parts, 130 parts, 150 parts, 170 parts, 190 parts, 200 parts, 210 parts or 230 parts. The inorganic filler can further improve the heat resistance, moisture and heat resistance and mechanical properties of the resin composition, and reduce the thermal expansion coefficient. If the amount of inorganic filler is too much, the dielectric loss tangent of the resin composition will increase, which is not conducive to signal transmission.
[0075] The present invention is not particularly limited to the type of inorganic filler, and exemplarily includes: any one or at least two combinations of silicon dioxide, aluminum hydroxide, magnesium hydroxide, boehmite, molybdenum oxide, zinc oxide, zinc molybdate, zinc borate, zinc stannate, titanium dioxide, strontium titanate, barium titanate, barium sulfate, clay, kaolin, talc, mica, boron nitride, aluminum nitride, silicon carbide, aluminum oxide, composite silicon powder, glass powder, short glass fiber or hollow glass. In order to make the resin composition have higher heat resistance, moisture and heat resistance and dimensional stability, it is preferably any one or at least two combinations of silicon dioxide, aluminum hydroxide, magnesium hydroxide, boehmite, boron nitride, aluminum nitride, silicon carbide, aluminum oxide, composite silicon powder, glass powder, short glass fiber or hollow glass. Wherein, the silicon dioxide can be crystalline silica, fused silica, amorphous silica, spherical silica or hollow silica, etc., and more preferably spherical silica.
[0076] The average particle size of the inorganic filler (D 50 ) is not particularly limited, but from the perspective of dispersibility, the average particle size (D 50) is preferably 0.01-20 microns, for example 0.02 micron, 0.05 micron, 0.1 micron, 0.2 micron, 0.8 micron, 1.5 micron, 2.1 micron, 2.6 micron, 3.5 micron, 4.5 micron, 5.2 micron, 5.5 micron, 6 micron, 6.5 micron, 7 micron, 7.5 micron, 8 micron, 8.5 micron, 9 micron, 9.5 micron, 12 micron, 13.5 micron, 15 micron, 17.5 micron, 18 micron, 19.5 micron, more preferably 0.1-10 micron. Inorganic fillers of different types, different particle size distributions or different average particle diameters can be used alone or in combination as needed.
[0077] Preferably, the resin composition further comprises 0.01 to 10 parts of a coupling agent by weight, for example, the coupling agent may be 0.03, 0.05, 0.1, 0.3, 0.5, 1, 2, 3, 4, 5, 6, 7, 8 or 9 parts, etc., and 0.1 to 6 parts of a coupling agent are further preferred; the coupling agent can improve the compatibility of the inorganic filler with the resin composition.
[0078] Preferably, the coupling agent comprises a silane coupling agent.
[0079] The present invention does not particularly limit the type of silane coupling agent, and illustratively includes but is not limited to: any one of epoxy silane coupling agent, amino silane coupling agent, vinyl silane coupling agent, styrene silane coupling agent, isobutylene silane coupling agent, acryl silane coupling agent, urea silane coupling agent, mercapto silane coupling agent, chloropropyl silane coupling agent, sulfide silane coupling agent or isocyanate silane coupling agent, or a combination of at least two thereof.
[0080] Preferably, the resin composition further comprises a flame retardant. The flame retardant is not particularly limited, and can be selected from halogen or non-halogen flame retardants that are soluble or insoluble in an organic solvent. Exemplarily, the non-halogen flame retardant includes an inorganic phosphorus flame retardant, an organic phosphorus flame retardant, a metal hydrate, and the like.
[0081] From the perspective of environmental issues and excellent dielectric properties, the flame retardant is preferably an organophosphorus flame retardant. Exemplarily, the organophosphorus flame retardant includes aromatic phosphates, monosubstituted phosphonic acid diesters, disubstituted phosphinates, metal salts of disubstituted phosphinates, organic nitrogen-containing phosphorus compounds, cyclic organophosphorus compounds, and the like.
[0082] For example, the aromatic phosphates include triphenyl phosphate, tricresyl phosphate, tri(xylene) phosphate, cresyl diphenyl phosphate, cresyl di-2,6-xylene phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di(2,6-dimethylphenyl) phosphate), 4,4'-biphenyl bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(di(2,6-dimethylphenyl) phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis(diphenyl phosphate), etc.; the monosubstituted phosphonic acid diesters include divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl) phenylphosphonate, etc.; the disubstituted phosphinates include Phenyl diphenylphosphinate, methyl diphenylphosphinate, etc.; the metal salt of the disubstituted phosphinate includes metal salts of dialkylphosphinate, metal salts of diallylphosphinate, metal salts of divinylphosphinate, metal salts of diarylphosphinate, etc.; the organic nitrogen-phosphorus compound includes phosphazene compound, melamine phosphate, melamine polyphosphate, melamine pyrophosphate, etc.; the cyclic organic phosphorus compound includes 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10 oxide, etc.
[0083] The flame retardants may be used alone or in combination of at least two kinds.
[0084] There is no particular restriction on the amount of the flame retardant. Preferably, when a phosphorus-based flame retardant is used in the resin composition of the present invention, the amount of the flame retardant is preferably 0.2 to 5 parts by weight, more preferably 0.3 to 3 parts by weight, and further preferably 0.5 to 3 parts by weight, based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group, the cross-linking agent containing the structure shown in Formula I in the molecular structure, and the flame retardant. When the weight of phosphorus atoms is within this range, a good balance can be achieved in flame retardancy, processability, and heat resistance.
[0085] Considering the requirements of preparation and processing, the resin composition further includes a solvent, and the amount of the solvent is not limited, as long as the components in the resin composition can be dissolved and dispersed and do not separate during mixing.
[0086] The type of the solvent is not particularly limited, and includes any one or a combination of at least two of alcohol solvents, ether solvents, aromatic hydrocarbon solvents, ester solvents, ketone solvents or nitrogen-containing solvents, preferably any one or a combination of at least two of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene or xylene.
[0087] In another aspect, the present invention provides a prepreg, comprising a substrate, and the resin composition according to the first aspect attached to the substrate by impregnation and drying.
[0088] Preferably, the substrate includes any one of glass fiber cloth, organic fiber cloth or glass fiber paper, and more preferably glass fiber cloth.
[0089] The glass fiber cloth includes Q-glass fiber cloth, E-glass fiber cloth, D-glass fiber cloth, L-glass fiber cloth, M-glass fiber cloth, S-glass fiber cloth, T-glass fiber cloth or NE-glass fiber cloth, etc.
[0090] The organic fiber cloth includes polyimide fiber cloth, polyamide fiber cloth, polyester fiber cloth, polyphenylene ether fiber cloth or liquid crystal polymer fiber cloth.
[0091] Illustratively, the method for preparing the prepreg comprises: impregnating a substrate with a resin glue of the resin composition, and then drying to obtain the prepreg.
[0092] The solvent in the resin glue is not particularly limited, and is preferably any one of acetone, butanone, methyl ethyl ketone, cyclohexanone, toluene or xylene, or a combination of at least two thereof.
[0093] Preferably, the drying temperature is 100-180°C, for example, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, etc.
[0094] Preferably, the drying time is 1 to 10 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0095] In another aspect, the present invention provides a metal foil-clad laminate, comprising at least one prepreg as described above, and a metal foil disposed on one side or both sides of the prepreg.
[0096] The metal foil may be copper foil, aluminum foil, nickel foil or alloy foil; preferably, the metal foil is copper foil.
[0097] Preferably, the number of prepregs in the metal foil-clad laminate is 1 to 20, for example, 1, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19.
[0098] Exemplarily, the preparation method of the metal-clad laminate is: laminating metal foil on one side or both sides of a prepreg, curing, and obtaining the metal-clad laminate; or, stacking at least two prepregs, and then laminating metal foil on one side or both sides of the stacked prepregs, curing, and obtaining the metal-clad laminate.
[0099] Preferably, the curing is carried out in a press.
[0100] Preferably, the curing temperature is 200-250°C, for example, 205°C, 210°C, 212°C, 215°C, 218°C, 220°C, 223°C, 225°C, 228°C, 230°C, 235°C, 240°C or 245°C, and more preferably 210-230°C.
[0101] Preferably, the curing pressure is 10-60 kg / cm 2 , for example 15kg / cm 2 , 20kg / cm 2 , 25kg / cm 2 、30kg / cm 2 、35kg / cm 2 , 40kg / cm 2 , 45kg / cm 2 , 50kg / cm 2 or 55kg / cm 2 wait.
[0102] Preferably, the curing time is 30 to 180 min, for example, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min or 175 min, etc.
[0103] In another aspect, the present invention provides a printed wiring board, comprising at least one prepreg as described above or one metal foil-clad laminate as described above.
[0104] Compared with the prior art, the present invention has the following beneficial effects:
[0105] (1) The resin composition provided by the present invention comprises a modified maleimide compound, a polyphenylene ether containing an unsaturated group, and a cross-linking agent having a structure represented by Formula I in its molecular structure. By screening and synergistically compounding the three components, the water absorption rate, planar thermal expansion coefficient, and dielectric loss tangent of the resin composition are significantly reduced, while having a higher glass transition temperature and maintaining low dielectric properties after absorbing water.
[0106] (2) The present invention further optimizes the components and dosages to make the prepreg, laminate and metal foil-clad laminate prepared by the resin composition have a glass transition temperature of ≥211°C and can reach 309°C, a planar thermal expansion coefficient as low as 7-14 ppm / °C, a water absorption rate of ≤0.16%, and a dielectric loss tangent of ≤0.0057 at 10 GHz, and has both low planar thermal expansion coefficient and low water absorption rate, excellent dielectric properties and dimensional stability, and can inhibit the D f Changes (△D after water absorption) f As low as 0.0001~0.0006), it is especially suitable for higher-level high-frequency and high-speed packaging. DETAILED DESCRIPTION
[0107] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0108] Preparation Example 1
[0109] A modified maleimide compound comprises an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule, and the preparation method is as follows:
[0110] Into a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser were added 9 parts by weight of a siloxane compound containing two primary amino groups (X-22-161B of Shin-Etsu Chemical Co., Ltd.), 1 part by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 30 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether, the mixture was stirred and heated to 115° C., and then the temperature was maintained for reaction for 4 hours to obtain the modified maleimide compound, hereinafter referred to as BMI A1.
[0111] Preparation Example 2
[0112] A modified maleimide compound comprises an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule, and the preparation method is as follows:
[0113] In a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser, 4 parts by weight of an amine compound containing two primary amino groups (BAPP of Wakayama Seika Industries, Ltd., 2,2-bis(4-(4-aminophenoxy)phenyl)propane), 36 parts by weight of a maleimide compound (BMI-1000 of Yamato Chemical Industries, Ltd., bis(4-maleimidophenyl)methane) and 40 parts by weight of propylene glycol monomethyl ether were added, the temperature was raised to 115° C. with stirring, and the reaction was maintained at this temperature for 4 hours to obtain the modified maleimide compound, hereinafter referred to as BMI A2.
[0114] Preparation Example 3
[0115] A modified maleimide compound comprises an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule, and the preparation method is as follows:
[0116] Into a three-necked flask equipped with a thermometer, a stirring paddle and a reflux condenser were added 9.5 parts by weight of a siloxane compound containing two primary amino groups (X-22-161A of Shin-Etsu Chemical Co., Ltd.), 0.5 parts by weight of an amine compound containing two primary amino groups (Kayahard AA of Nippon Kayaku Kogyo Co., Ltd., 3,3'-diethyl-4,4'-diaminodiphenylmethane), 30 parts by weight of a maleimide compound (BMI-4000 of Yamato Chemical Co., Ltd., 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane) and 40 parts by weight of propylene glycol monomethyl ether, the mixture was stirred and heated to 115° C., and then the temperature was maintained for reaction for 4 hours to obtain the modified maleimide compound, hereinafter referred to as BMI A3.
[0117] The experimental materials involved in the following embodiments and comparative examples of the present invention include:
[0118] (1) Maleimide compounds
[0119] a) Modified maleimide compounds
[0120] BMI A1, Preparation Example 1;
[0121] BMI A2, Preparation Example 2;
[0122] BMI A3, Preparation Example 3;
[0123] b) Unmodified maleimide compounds
[0124] BMI-4000, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, Yamato Chemical Industry Co., Ltd.
[0125] (2) Polyphenylene ether containing unsaturated groups
[0126] OPE-2st 2200, polyphenylene ether containing vinyl benzyl groups at the end, Mitsubishi Chemical Corporation;
[0127] SA-9000, polyphenylene ether containing methacrylate groups at the end, M n About 1900-2300, Saudi Basic Industries Corporation.
[0128] (3) Cross-linking agent
[0129] a) a cross-linking agent having a molecular structure of formula I
[0130] 9,9-Bis(4-(2-acryloyloxyethoxy)phenyl)fluorene, Hubei Xinkang Pharmaceutical Chemical Co., Ltd.;
[0131] 9,9-Bis(4-epoxypropyloxyphenyl)fluorene, Huanghua Xinnuolixing Fine Chemical Co., Ltd.;
[0132] b) a cross-linking agent having no structure shown in formula I in its molecular structure
[0133] Ethoxylated bisphenol A diacrylate, BPA3EODA, Guangzhou Sanwang Chemical Materials Co., Ltd.
[0134] (4) Auxiliary cross-linking agent
[0135] NK ESTER DCP, tricyclodecane dimethanol methacrylate, Shin-Nakamura Chemical Industry Co., Ltd.
[0136] (5) Polyolefin resin
[0137] Tuftec H1051, hydrogenated styrene-butadiene copolymer, Asahi Kasei Chemicals Corporation.
[0138] (6) Curing accelerator
[0139] Triginox 311, 3,3,5,7,7-pentamethyl-1,2,4-trioxypropane, Akzo Nobel, USA.
[0140] (7) Inorganic fillers
[0141] SC2300-SVJ, spherical silica surface treated with vinyl silane coupling agent, median particle size D50 is 0.5 μm, Japan Admatechs Co., Ltd.
[0142] (8) Coupling agent
[0143] KBM-573, N-phenyl-3-aminopropyltrimethoxysilane, Shin-Etsu Corporation, Japan.
[0144] Example 1
[0145] The present embodiment provides a resin composition, which includes the following components in parts by weight: 40 parts of a modified maleimide compound BMI A1, 40 parts of an unsaturated group-containing polyphenylene ether OPE-2st 2200, 20 parts of 9,9-bis(4-(2-acryloyloxyethoxy)phenyl)fluorene, 2 parts of a curing accelerator Triginox 311, 2 parts of a coupling agent KBM-573, and 130 parts of an inorganic filler SC2300-SVJ.
[0146] This embodiment also provides a metal foil-clad laminate, and the specific preparation method is as follows:
[0147] (1) The resin composition provided in this embodiment, toluene and butanone are mixed, fully dissolved and evenly dispersed to obtain a resin glue solution with a solid content of 60%;
[0148] (2) impregnating glass fiber cloth (Hubel 3313, Taiwan, China) with the resin glue obtained in step (1), heating and drying in a blast oven at 130° C. for 4 min, so that the varnish state of the resin composition is converted into a semi-cured state of the resin composition, the unit weight of which is 190 g / m 2 , the average thickness is controlled to be 100 μm, and a prepreg is obtained;
[0149] (3) Two (or eight) prepregs obtained in step (2) are stacked, and electrolytic copper foil with a thickness of 18 μm is pressed on the upper and lower sides thereof. The prepregs are heated in a press at 220° C. and 45 kg / cm 2 After curing for 2 hours, a copper-clad laminate with a core board thickness of 0.20 mm (or 0.80 mm) was obtained.
[0150] After etching the gold copper foil of the copper-clad laminate, a laminate with a thickness of 0.20 mm (or 0.80 mm) is obtained.
[0151] Examples 2 to 11, Comparative Examples 1 to 7
[0152] A resin composition, the components and contents of which are shown in Table 1 and Table 2; the dosage units of each component in Table 1 and Table 2 are all "parts".
[0153] Table 1
[0154]
[0155]
[0156] Table 2
[0157]
[0158]
[0159] The above resin composition was made into a metal foil-clad laminate according to the method in Example 1. The properties of the laminate and the test methods of the experimental materials are as follows:
[0160] (1) Glass transition temperature T g : A laminate with a length of 60 mm, a width of 10 mm, and a thickness of 0.80 mm was taken as a sample and measured using a dynamic mechanical thermal analyzer (DMA) with a heating rate of 10°C / min. The result was taken as the transition peak temperature of tanδ in °C.
[0161] (2) Planar thermal expansion coefficient (XY-CTE): A laminate with a length of 60 mm, a width of 4 mm, and a thickness of 0.20 mm was taken as a sample, with the glass fiber warp direction in the Y direction and the glass fiber weft direction in the X direction. The sample was dried in an oven at 105°C for 1 hour and then cooled to room temperature in a desiccator. The measurement was performed using the thermal mechanical analysis method (TMA) with a heating rate of 10°C / min, from room temperature to 300°C, and two heatings were performed. After the first heating was completed and cooled to room temperature, the sample was re-set for the second heating. The result was the planar thermal expansion coefficient at the second heating from 50°C to 130°C, and the unit was ppm / °C.
[0162] (3) Dielectric constant (D k ) and dielectric loss tangent (D f ): A laminate with a length of 100 mm, a width of 100 mm, and a thickness of 0.20 mm was taken as a sample. The sample was ultrasonically cleaned in deionized water to remove impurities on the surface, and then dried in an oven at 105°C for 1 hour and cooled to room temperature in a desiccator. The dielectric constant (D k ) and dielectric loss tangent (D f ).
[0163] Dielectric loss tangent after water absorption (D f ): Take the loss tangent of the above test medium (D f ) samples were placed in an environment with a temperature of 25°C and a humidity of 55% for one week, and the dielectric loss tangent (D f ).
[0164] △D f : Dielectric loss tangent after water absorption (D f )-Dielectric loss tangent before water absorption (D f ).
[0165] (4) Water absorption rate: A laminate with a length of 50 mm, a width of 50 mm and a thickness of 0.80 mm was taken as a sample. After the impurities on the surface of the sample were ultrasonically cleaned in deionized water, the sample was dried in an oven at 105°C for 1 hour and the weight was weighed as W0. The sample was soaked in water at a temperature of 25-30°C for 24 hours, the sample was taken out and naturally dried, and the weight was weighed as W1. Water absorption rate = 100% × (W1-W0) / W0.
[0166] (5) Number average molecular weight: the test method is GB / T 21863-2008, and it is measured by gel permeation chromatography based on polystyrene calibration.
[0167] The test results are shown in Table 3:
[0168] Table 3
[0169]
[0170]
[0171] According to the performance test data in Table 3, the resin compositions provided by Examples 1 to 11 of the present invention are used to prepare metal foil-clad laminates, and the glass transition temperature reaches above 211°C, and can reach 309°C, the plane thermal expansion coefficient is as low as 7 to 14 ppm / °C, the water absorption rate is 0.07 to 0.16%, and the dielectric loss tangent at 10 GHz is 0.0045 to 0.0057. It has a low plane thermal expansion coefficient and low water absorption rate, and exhibits excellent dielectric properties and dimensional stability, and inhibits the D f Changes in (△D f As low as 0.0001~0.0006), it is especially suitable for higher-level high-frequency and high-speed packaging.
[0172] If the crosslinking agent having the structure shown in Formula I in the molecular structure of the resin composition is replaced with other aromatic diacrylates (Comparative Example 2) or the amount of the crosslinking agent having the structure shown in Formula I in the molecular structure is too low (Comparative Example 4), the water absorption rate of the laminate increases, the planar thermal expansion coefficient and the dielectric loss tangent increase, and the D after water absorption cannot be effectively inhibited. f If the amount of the cross-linking agent containing the structure shown in Formula I in the molecular structure is too high (Comparative Example 5), the dielectric properties of the laminate will be reduced, and the reliability of the resin composition, the laminate, the metal foil-clad laminate and the printed circuit board will be affected due to insufficient curing.
[0173] If the modified maleimide compound is not used in the resin composition (Comparative Example 3), the planar thermal expansion coefficient of the laminate is high, the dimensional stability is poor, and the D after water absorption cannot be effectively suppressed. fIf the amount of the modified maleimide compound in the resin composition is too high (Comparative Example 6), even if the content of the cross-linking agent containing the structure represented by Formula I in the molecular structure is within an appropriate range, the laminate cannot exhibit low water absorption, low dielectric constant, and low dielectric loss characteristics; if the amount of the modified maleimide compound in the resin composition is too low (Comparative Example 7), the glass transition temperature of the laminate drops sharply, and the laminate does not have the characteristic of low planar thermal expansion coefficient, and does not meet the requirements of the packaging carrier.
[0174] If the resin composition does not use polyphenylene ether containing unsaturated groups in its molecular structure (Comparative Example 1), the dielectric constant and dielectric loss tangent of the laminated board increase, and the requirements of the high-speed and high-frequency packaging substrate are not met.
[0175] The applicant declares that the present invention illustrates a resin composition and its application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises the following components in parts by weight: 10 to 70 parts of a modified maleimide compound, 10 to 75 parts of a polyphenylene ether containing an unsaturated group, and 5 to 30 parts of a crosslinking agent; The crosslinking agent is 9,9-bis(4-(2-acryloyloxyethoxy)phenyl)fluorene or 9,9-bis(4-epoxypropyloxyphenyl)fluorene; The modified maleimide compound includes an addition reaction product of a maleimide compound a1 containing at least two N-substituted maleimide groups in one molecule and an amine compound a2 containing at least two primary amino groups in one molecule.
2. The resin composition according to claim 1, characterized in that The maleimide compound a1 contains two N-substituted maleimide groups in one molecule.
3. The resin composition according to claim 1, characterized in that The maleimide compound a1 includes N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-(1,3-(2-methylphenylene))bismaleimide, N,N'-(1,3-(4-methylphenylene))bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, bis(3- ethyl-5-methyl-4-maleimidophenyl)methane, bis(3-ethyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(4-maleimidophenoxy)benzene, 1,3-bis(3-maleimidophenyl) oxy)benzene, bis(4-(3-maleimidophenoxy)phenyl)methane, bis(4-(4-maleimidophenoxy)phenyl)methane, 1,1-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(3-maleimidophenoxy)phenyl)ethane, 1,2-bis(4-(4-maleimidophenoxy)phenyl)ethane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane Any one or a combination of at least two of bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(3-maleimidophenoxy)phenyl)butane, 2,2-bis(4-(4-maleimidophenoxy)phenyl)butane, 4,4'-bis(3-maleimidophenoxy)biphenyl, 4,4'-bis(4-maleimidophenoxy)biphenyl, bis(4-(3-maleimidophenoxy)phenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)ketone, bis(4-(3-maleimidophenoxy)phenyl)ether or bis(4-(4-maleimidophenoxy)phenyl)ether.
4. The resin composition according to claim 3, characterized in that The maleimide compound a1 is any one of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane or 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane or a combination of at least two thereof.
5. The resin composition according to claim 1, characterized in that The amine compound a2 includes a siloxane compound containing at least two primary amino groups, diaminobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, diaminodiphenylmethane, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminobiphenyl methylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, diaminodiphenyl ether, 3,3'-dimethoxy-4,4'-diaminodiphenylmethane aminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenyl ether, 1,3 - any one of bis(4-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(3-aminophenoxy)phenyl)propane, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diaminobiphenyl or 4,4'-diamino-3,3'-dihydroxybiphenyl, or a combination of at least two thereof.
6. The resin composition according to claim 5, characterized in that The amine compound a2 is any one of a siloxane compound containing at least two primary amino groups, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, or 2,2-bis(4-(4-aminophenoxy)phenyl)propane, or a combination of at least two thereof.
7. The resin composition according to claim 1, characterized in that The amine compound a2 includes a siloxane compound having two primary amino groups in one molecule.
8. The resin composition according to claim 7, characterized in that The amine compound a2 includes a siloxane compound having two primary amino groups at the molecular terminals.
9. The resin composition according to claim 5, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the crosslinking agent, the amount of the siloxane compound is 1 to 30 parts.
10. The resin composition according to claim 9, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing unsaturated groups and the crosslinking agent, the amount of the siloxane compound is 2 to 15 parts.
11. The resin composition according to claim 1, characterized in that The polyphenylene ether containing unsaturated groups has a structure as shown in Formula II: Wherein, R3, R4, R5, and R6 are each independently selected from hydrogen, C1-C8 straight chain or branched chain alkyl; m and n are each independently selected from 0 to 100, and m and n are not 0 at the same time; A1 and A2 are each independently selected from any one of the following groups: p and q are each independently selected from integers of 0 to 8; R7, R8, and R9 are each independently selected from hydrogen, a C1-C8 straight or branched chain alkyl group; M is selected from carbonyl, C6-C18 arylene, C1-C10 straight or branched alkylene; Z is selected from X is selected from C1-C20 straight or branched alkylene, C3-C20 cycloalkylene, C2-C20 heterocycloalkylene, or one or at least two non-adjacent -CH2- in the C1-C20 straight or branched alkylene are replaced by -O-, -S-, -CO-, Substituted groups; R Z1 , R Z2 , R Z3 , R Z4 , R Z5 , R Z6 , R Z7 , R Z8 , R N , R P , R S1 , R S2 Each is independently selected from hydrogen, C1-C8 straight chain or branched alkyl.
12. The resin composition according to claim 11, characterized in that Said A1 and A2 are each independently selected from Any one of .
13. The resin composition according to claim 11, characterized in that At least one of A1 and A2 is 14. The resin composition according to claim 1, characterized in that The number average molecular weight of the polyphenylene ether containing unsaturated groups is 500-3000.
15. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the crosslinking agent, the amount of the modified maleimide compound is 10 to 70 parts.
16. The resin composition according to claim 15, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing an unsaturated group and the crosslinking agent, the amount of the modified maleimide compound is 10 to 50 parts.
17. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing unsaturated groups and the crosslinking agent, the amount of the polyphenylene ether containing unsaturated groups is 10 to 75 parts.
18. The resin composition according to claim 17, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing unsaturated groups and the crosslinking agent, the amount of the polyphenylene ether containing unsaturated groups is 10 to 50 parts.
19. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the total amount of the modified maleimide compound, the polyphenylene ether containing unsaturated groups and the crosslinking agent, the amount of the crosslinking agent is 5 to 30 parts.
20. The resin composition according to claim 1, characterized in that The resin composition further comprises 0.5 to 40 parts by weight of an auxiliary crosslinking agent.
21. The resin composition according to claim 20, characterized in that The auxiliary cross-linking agent includes a cross-linking agent having a carbon-carbon unsaturated double bond in the molecule and / or a cyanate ester.
22. The resin composition according to claim 21, characterized in that The crosslinking agent having carbon-carbon unsaturated double bonds in the molecule includes any one of a multifunctional vinyl compound, an allyl compound, tricyclodecane dimethanol methacrylate, a trialkenyl isocyanurate compound, an acenaphthylene compound or polybutadiene, or a combination of at least two thereof.
23. The resin composition according to claim 22, characterized in that The allyl compound includes triallyl isocyanurate.
24. The resin composition according to claim 20, characterized in that Based on 100 parts by weight of the total amount of the cross-linking agent and the auxiliary cross-linking agent, the amount of the cross-linking agent is ≥50 parts.
25. The resin composition according to claim 24, characterized in that Based on 100 parts by weight of the total amount of the crosslinking agent and the auxiliary crosslinking agent, the amount of the crosslinking agent is 70 to 100 parts.
26. The resin composition according to claim 1, characterized in that The resin composition further comprises 2 to 30 parts by weight of polyolefin resin.
27. The resin composition according to claim 1, characterized in that The resin composition further comprises 0.01 to 5 parts by weight of a curing accelerator.
28. The resin composition according to claim 1, characterized in that The resin composition further comprises 5 to 250 parts by weight of inorganic filler.
29. The resin composition according to claim 1, characterized in that The resin composition further comprises 0.01 to 10 parts by weight of a coupling agent.
30. The resin composition according to claim 29, characterized in that The coupling agent includes a silane coupling agent.
31. A prepreg, characterized in that The prepreg comprises a substrate, and the resin composition according to any one of claims 1 to 30 attached to the substrate by impregnation and drying.
32. The prepreg according to claim 31, characterized in that The substrate includes any one of glass fiber cloth, organic fiber cloth or glass fiber paper.
33. A metal foil-clad laminate, characterized in that: The metal foil-clad laminate includes at least one prepreg according to claim 31 or 32, and a metal foil disposed on one side or both sides of the prepreg.
34. The metal-clad laminate according to claim 33, characterized in that: The metal foil is copper foil.
35. A printed circuit board, characterized in that: The printed wiring board comprises at least one prepreg as claimed in claim 31 or 32 or a metal foil-clad laminate as claimed in claim 33 or 34.
Citation Information
Patent Citations
Halogen-free resin composition, prepreg and laminated board made from the same
CN102850766A
Thermosetting hydrocarbon polymer composition, and prepreg and thermosetting copper-clad plate prepared therefrom
CN110605880A
Resin composition, and prepreg and circuit material using same
CN111393724A
Resin composition, coating film, and insulating film for touch panel
CN103857750A
Resin composition, and printed wiring board, laminated sheet, and prepreg using same
CN105647118A